Pemanfaatan Ekstrak Kulit Buah Naga (Hylocereus polyrhizus) Sebagai Bahan Aktif Pembuatan Sabun Cair Alami - Januarti, Melinda; Husni, Patihul; Christiningtyas Eryani, Mikhania (JURNAL FARMASI GALENIKA, 2024)
Nowadays, many people are paying attention to the benefits of natural soap because it is believed to be gentler on the skin and environmentally friendly. This research aims to determine the formulation of natural liquid soap with the addition of dragon fruit peel extract that is effective and meets the requirements. The method used is an experimental method by formulating a natural liquid soap containing 0.5% dragon fruit peel extract as the active ingredient and adding cocamid-DEA as a foam stabilizer in variations of 1%, 3%, and 5%. The tests conducted include organoleptic tests, pH tests, foam height tests, viscosity tests, and skin condition tests. Research shows that the natural liquid soap produced has characteristics of a reddish-purple color, a distinctive scent, and varying consistency depending on the concentration of cocamid-DEA added, where F3 has the highest viscosity at 528.9 mPa, F2 at 525.7 mPa, and F1 at 428.9 mPa. From the pH testing results, F1 has a pH of 8, while F2 and F3 have a pH of 9. In the foam height test, all formulas met the soap foam height requirement of 1.3-22 cm. The first formulation of natural liquid soap with the addition of dragon fruit peel extract as an active ingredient, based on organoleptic tests, pH tests, viscosity, and foam height tests, produced the best results and met the requirements.